PERAN ORANG MUDA KATOLIK DALAM MEMELIHARA BUMI SEBAGAI RUMAH UMAT MANUSIA - Clara R.P. Ajisuksmo; Teresa M. Rosario; Yeremias S.I. Soge (Seminar Nasional Penelitian dan Abdimas, 2023)
In Pope Francis Laudato Si' Encyclical, the Catholic Church is called to reflect and consider on care for the earth as the home of humanity. The Laudato Si' also talks about social, economic, and respect for the cultural existence of indigenous peoples and local wisdom. There are seven dimensions highlighted in the encyclical, namely response to the cry of the earth, response to the cry of the poor, ecological economics, adoption of sustainable lifestyles, ecological education, ecological spirituality, and community resilience and empowerment. Catholic youths are expected to become agents of change who seek to create a better world. This research provides an overview of the knowledge, attitudes and practices of how Catholic youth play a role in protecting and caring for the earth as the home of mankind. This research also identifies supporting and hindering factors in caring for the environment. This research was conducted in Sungai Utik West Kalimantan by conducting Focus Group Discussions and Key Informant Interviews. The result indicated that what is needed to improve is the adoption of sustainable lifestyles.